Berinovasi Pasca Covid-19 Melalui Pengelolaan Sampah Desa Bandaran - Wahyu Maulana; Rohmaniyah Rohmaniyah (LPPM Universitas Trunojoyo Madura, 2022)
One effective way to reduce piles of waste is to manage it into innovative handicraft products. In addition to having an impact on cleanliness and health, the community also has economic value activities so that they become passive income. This year's KKN theme is